Is three-piece maxillary segmentation surgery a stable procedure? - Kato, Renata Mayumi [UNESP]; Gonçalves, João Roberto [UNESP]; Ignácio, Jaqueline [UNESP]; Wolford, Larry; de Mello, Patricia Bicalho; Parizotto, Julianna [UNESP]; Bianchi, Jonas [UNESP] (Korean Association of Orthodontists, 2024)
Objective: The number of three-piece maxillary osteotomies has increased over the years; however, the literature remains controversial. The objective of this study was to evaluate the skeletal stability of this surgical modality compared with that of one-piece maxillary osteotomy. Methods: This retrospective cohort study included 39 individuals who underwent Le Fort I maxillary osteotomies and were divided into two groups: group 1 (three pieces, n = 22) and group 2 (one piece, n = 17). Three cone-beam computed tomography scans from each patient (T1, pre-surgical; T2, post-surgical; and T3, follow-up) were used to evaluate the three-dimensional skeletal changes. Results: The differences within groups were statistically significant only for group 1 in terms of surgical changes (T2-T1) with a mean difference in the canine region of 3.09 mm and the posterior region of 3.08 mm. No significant differences in surgical stability were identified between or within the groups. The mean values of the differences between groups were 0.05 mm (posterior region) and –0.39 mm (canine region). Conclusions: Our findings suggest that one-and three-piece maxillary osteotomies result in similar post-surgical skeletal stability.
Keywords: Maxillary osteotomy; Surgical procedures; Tomography